One-Pot Synthesis and Characterization of Gold Nanoparticle-Embedded Natural Magnetic Particles/Chitosan Composite - Martha, Annisa Afra (Solid State Phenomena, 2022)
This research synthesized natural magnetic particles/chitosan/gold nanoparticles composites (NMP/Chi/AuNPs) using a green method. AuNPs were synthesized using chitosan as a reducing agent and stabilizer in one step. The obtained AuNPs were characterized using UV-Vis spectrophotometer and TEM. Results showed that AuNPs were spherical with an average of 14.99 nm and absorbed at visible light (~530 nm). Then, AuNPs were impregnated on NMP/Chi at room temperature. The impregnation results were characterized using FTIR, XRD, and TEM. In the IR spectra of NMP/Chi and NMP/Chi/AuNPs(1.25), the C=O(-NHCOCH3) stretching vibrations were shown at 1604 and 1632 cm-1 . The NMP/Chi/AuNPs(1.25) showed a decrease in intensity and the peak shift to 1395 cm-1, stretching vibration of CN in the chitosan structure. Fe-O vibrations of Fe3O4 in NMP/Chi and NMP/Chi/AuNPs(1.25) were shown at 566 and 510 cm-1 . The intensity peak shift and decrease indicate an interaction between AuNPs and NMP/Chi. The XRD NMP/Chi/AuNPs(1.25) characterization showed that the diffraction peak at 2Ө 35.44° decreased in intensity, resulting in a decrease in crystallinity caused by impregnated AuNPs and the destruction of hydrogen bonds. The new diffraction peak at 2Ө 38.24° indicates the presence of AuNPs. TEM analysis showed an amorphous layer around the NMP, and the average size of AuNP in the NMP/Chi/AuNP composite was 23.01 nm. The presence of AuNP makes NMP/Chi/AuNPs potential an antibacterial agent. © 2022 Trans Tech Publications Ltd, Switzerland